A Stable Polyaniline‐Benzoquinone‐Hydroquinone Supercapacitor. (13th June 2014) - Vonlanthen, David; Lazarev, Pavel; See, Kimberly A.; Wudl, Fred; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> A Polyaniline‐Supercapacitor with quinone electrolytes remains stable over 50 000 galvanostatic charge‐discharge cycles. The quinones provide superior stability by preventing the conversion of porous polyaniline to a highly reactive state. Our work shows that highly stable polymer‐supercapacitors can be engineered by combining electrochemically active polymers and redox‐active electrolytes with concerted electrochemical properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>